Effects of plyometric warm-up performed with different resistances on jumping performance as post-activation potentiation - Harmanci, H.; Demirel, P.; Koç, H.; Tekin, R. (Journal of Human Sport & Exercise, 2024)
The purpose of this study was to investigate the effect of plyometric warm-up with different resistances as post activation potentiation stimulus on vertical jump performance. Fifteen athletes from short and middle distance branches of athletics who have been training regularly for at least 5 years and at least 5 days a week attended the study voluntarily. The athletes in this study were warmed up for 5 minutes at a speed of 8 km/h on a treadmill, followed by 5 minutes of passive rest. Completing 5 minutes of passive rest, the athletes were randomly sampled and any of the 50 lb, 60 lb, 70 lb, 80 lb resistance or non-resistance warm-up protocols consisting of 3 sets on the vertimax device were carried out. After warming up, 5 minutes of passive rest was given and then squat jump (SJ) and countermovement jump tests were performed. Repeated measures ANOVA test was conducted in the analyses of the measurements of jump distance and power of the athletes participating in this study both without resistance and after the applied resistances. Significant differences were observed in SJ and CMJ values after PAP warm-up without and with resistance (p < .05). The height and power values of SJ after PAP warm-up with 70 lb and 80 lb resistance bands were found significantly higher than those without resistance (p < .05). Furthermore, the height and power values of CMJ after PAP warm-up with 80 lb resistance bands were found significantly higher than the values of warm-up without resistance (p < .05). In conclusion, even though an increase in jump height and power values was observed with each resistance increment, significant increases in power and height values as a PAP response were achieved at 70 and 80 lb resistance for SJ and 80 lb resistance for CMJ.